2016
DOI: 10.2147/ijn.s116347
|View full text |Cite
|
Sign up to set email alerts
|

Lx2-32c–loaded polymeric micelles with small size for intravenous drug delivery and their inhibitory effect on tumor growth and metastasis in clinically associated 4T1 murine breast cancer

Abstract: Lx2-32c is a novel taxane derivative with a strong antitumor activity. In this study, we developed Lx2-32c–loaded polymeric micelles (Lx2-32c-PMs) with small size and investigated their antitumor efficacy against tumor growth and metastasis on 4T1 murine breast cancer cell line with Cremophor EL–based Lx2-32c solution as the control. In this study, copolymer monomethoxy polyethylene glycol 2000 –polylactide 1300 was used to prepare Lx2-32c-PMs by film hydration met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…HKFs were inoculated in a plate with 96 wells and adjusted to 5.0×10 3 cells/well. After 24 hours' culture, the primary medium was replaced with the fresh medium containing a series of different test samples for another 24…”
Section: Cell Proliferation Inhibition Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…HKFs were inoculated in a plate with 96 wells and adjusted to 5.0×10 3 cells/well. After 24 hours' culture, the primary medium was replaced with the fresh medium containing a series of different test samples for another 24…”
Section: Cell Proliferation Inhibition Assaymentioning
confidence: 99%
“…Despite its efficacy in various diseases, PTX solvent used clinically contains a high concentration of Kolliphor EL (BSAF Company, Rheinland-Pfalz, German), 24 which can result in severe allergic reactions in patients. New drug delivery systems have been exploited to avoid hypersensitivity, eg, micelles, hydrogel, cyclodextrin nanocarriers, and liposomes.…”
Section: Introductionmentioning
confidence: 99%
“…27,28,37,38 In our previous study, we prepared docetaxel-loaded and Lx2-32c-loaded polymeric micelles. 39,40 Our results showed that polymeric micelles were stable and effective vectors for antitumor drugs.…”
Section: Introductionmentioning
confidence: 71%
“…Polymeric micelles containing LA67 were prepared using a film hydration method. 40 Briefly, 3 mg of LA67 and 150 mg of mPEG 2000 -PLA 1300 were dissolved in 3 mL of acetonitrile. Then, acetonitrile was removed by rotary evaporation in a water bath (50°C for 40 min).…”
Section: Preparation Of La67-pmsmentioning
confidence: 99%
See 1 more Smart Citation